Dampak Inflasi terhadap Kesejahteraan Masyarakat Perspektif Ekonomi Publik - Muhammad Raghid Alfatiy; Raihan Ade Ghuffar; Ahmad Wahyudi Zein (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This article comprehensively examines the impact of inflation on the welfare of Indonesian society from a public economics perspective. High inflation has been proven to erode purchasing power, widen economic inequality, and worsen quality of life, especially for fixed- and low-income groups. Rising prices of basic necessities force households to sacrifice spending on education and health, increasing the risk of poverty and lowering the human development index. Inflation also creates economic uncertainty, hampers investment, and triggers social conflict due to public unrest. Empirical studies indicate that every 1% increase in inflation can reduce real purchasing power by up to 2.3% and increase the number of poor people. To mitigate these regressive effects, integration of monetary, fiscal, and adaptive social protection policies is required. The experience of Indonesia and other countries underscores the importance of inter-institutional synergy and evidence-based interventions to maintain price stability and equitable welfare. In conclusion, inflation control should be seen as a long-term investment in human development and social justice, not merely as a macroeconomic stability target.